Asuhan Keperawatan Keluarga Pada Tahapan Keluarga Dewasa Pelepasan Dengan Pemberian Intervensi Kompres Hangat Serai Untuk Menurunkan Nyeri Gout Arthritis Pada Ny. U - Veronnicka Shintya Dewi; Alfika Safitri; M Hasan Basri; Rina Puspita Sari (Lembaga Pengembangan Kinerja Dosen, 2023)
Background: Family is two or more individuals who are joined by blood relations, marital relations or adoption and they live in one household, interact with each other and in their respective roles create and maintain culture. Signs and symptoms of gout are an increase in serum uric acid, severe pain that comes on suddenly, stiff movements, easily tired and lethargic. skin rash, sore throat, decreased appetite, red tongue. According to the World Health Organization (WHO) in 2019, 81% of sufferers of Gout Arthritis in Indonesia only 24% went to the doctor. while 71% tend to immediately consume over-the-counter pain relievers. Method: The method used in collecting this data is interview. Case study by carrying out nursing care for 5 days in the family of Mr. A especially Mrs. U by doing non-pharmacological therapy with warm compresses of lemongrass. Purpose: the purpose of doing this warm lemongrass compress is so that pain in the fingers and palms of the patient decreases. Results: After intervention with hot lemongrass compresses for 5 days, the pain was reduced, the patient's uric acid decreased to 4.7, and no tingling was felt. During the intervention, patients were also given education on how to manage their diet and a clean and healthy lifestyle. Conclusion: The conclusion drawn is the importance of regulating diet and maintaining a clean and healthy lifestyle in order to avoid diseases, especially gout.